Monetary Policy, Trend Inflation, and the Great Moderation: An Alternative Interpretation - Coibion, Olivier; Gorodnichenko, Yuriy (American Economic Review, 2011)
With positive trend inflation, the Taylor principle does not guarantee a determinate equilibrium. We provide new theoretical results on determinacy in New Keynesian models with positive trend inflation and new empirical findings on the Federal Reserve's reaction function before and after the Volcker disinflation to find that, (i) while the Fed likely satisfied the Taylor principle before Volcker, the US economy was still subject to self-fulfilling fluctuations in the 1970s, (ii) the US economy switched to determinacy during the Volcker disinflation, and (iii) the switch reflected changes in the Fed's response to macroeconomic variables and the decline in trend inflation. (JEL E12, E23, E31, E32, E52)